2018
DOI: 10.1063/1.5026719
|View full text |Cite
|
Sign up to set email alerts
|

Iso-thermal flow characteristics of rotationally symmetric jets generating a swirl within a cylindrical chamber

Abstract: We present a systematic experimental study of the interaction between four rotationally symmetric jets within a cylindrical chamber, under conditions relevant to a wide range of engineering applications, including the technology of a Hybrid Solar Receiver Combustor (HSRC). The HSRC geometry is simplified here to a cylindrical cavity with four inlet jets (representing four burners) which are configured in an annular arrangement and aligned at an inclination angle to the axis with a tangential component (azimuth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…The experimental studies of Boushaki and Sautet 4 employing Particle Image Velocimetry (PIV) showed that an increase in α j from 0 • to 30 • leads to a significant increase in the magnitude of mean and turbulent velocity fields within the jet merging region. Similarly, the PIV measurements of Long et al 10,11 found a strong dependence on jet angles (α j and θ j ) of the instantaneous and mean flow-fields generated with multiple symmetric jets. However, to the best of our knowledge, little or no information is available for the key geometrical parameters (e.g., L c and D c ) of the confined space for multiple jet configurations, although the aspect ratio of geometry has been found to have a significant influence on the flow-fields of free jet impingement [17][18][19] and cavity flow.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…The experimental studies of Boushaki and Sautet 4 employing Particle Image Velocimetry (PIV) showed that an increase in α j from 0 • to 30 • leads to a significant increase in the magnitude of mean and turbulent velocity fields within the jet merging region. Similarly, the PIV measurements of Long et al 10,11 found a strong dependence on jet angles (α j and θ j ) of the instantaneous and mean flow-fields generated with multiple symmetric jets. However, to the best of our knowledge, little or no information is available for the key geometrical parameters (e.g., L c and D c ) of the confined space for multiple jet configurations, although the aspect ratio of geometry has been found to have a significant influence on the flow-fields of free jet impingement [17][18][19] and cavity flow.…”
Section: Introductionmentioning
confidence: 64%
“…Another limit of these studies is that they have been performed almost exclusively for a single jet, which makes it difficult to directly apply to multiple confined jets. In our previous work, Long et al 11 revealed the presence of both an external and internal recirculation zone (ERZ and CRZ) within these configurations. The ERZ and CRZ regions are associated with the entrainment rate (or the recirculation rate) within the chamber, which is important for combustion stabilization and thermal efficiency.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations